The financialisation of the food system: Actors, backgrounds and implications - Clapp, Jennifer (Revista Española de Desarrollo y Cooperación, 2023)
This article examines the growing role of financial actors in the global food system in recent decades. It makes the case that financial actors have gained significant influence within that system. The article first outlines the key forces and actors involved in the recent rapid growth in financial investment in the agricultural sector. It then assesses the implications of the growing influence of this financial investment for global hunger and the environment.
Keywords: Financial actors; Food system; Commodities speculation; Land grabs; Biofuels